Responses of Symbiodiniaceae Shuffling and Microbial Community Assembly in Thermally Stressed Acropora hyacinthus - Zhu, Wentao; Liu, Xiangbo; Zhu, Ming; Li, Xinke; Yin, Hongyang; Huang, Jianzhong; Wang, Aimin; Li, Xiubao (Frontiers in Microbiology, 2022)
Although the importance of coral holobionts has been widely explored and reported, the relationship between the flexibility of the microbiome structure and the coral host is very complicated. In particular, while less is known about the community dynamics of holobionts and the stability of host-microbe interactions under different thermal stress. In this study, we holistically explored the physiology and growth of Acropora hyacinthus in response to increased temperatures (from 26°C to 33°C). We observed that bleaching corals with loss of algal symbionts therefore mainly catabolized lipids and proteins to maintain their survival, which reduced tissue biomass and growth rates. The increase in the diversity of Symbiodiniaceae and symbiont shuffling in community structure were caused through changes in the relative abundance of the thermally sensitive but dominant clade C symbionts and low abundance known as ‘background types”. Bacterial diversity showed a decreasing trend with increasing temperature, while there were no major shifts in the bacterial community structure. This may be due to the local adjustment of the abundance of specific microbial community members that may not affect the overall metabolic state of the coral holobiont, and there was no increase in the proportion of sequences identified as typically pathogenic or opportunistic taxa. Based on the Sloan neutral community model, it was found that neutral processes explained 42.37%-58.43% of bacterial community variation. The Stegen null model analysis showed that the stochastic processes explained a significantly higher percentage (73%-100%) of community assembly than deterministic processes in elevated temperature. The weak effect of temperature on bacterial community structures and assembly might be related to an increase of stochastic process dominance. The interaction of bacterial communities exhibited a fluctuating and simplistic trend with increasing temperature. Increases in temperature were sufficient to establish a high stability of bacterial networks, and nonlinear response was found between the complexity and stability of the networks. This study provides new insights into successive changes in scleractinian coral host and holobionts in response to increased temperatures, especially the contribution of community assembly process and species coexistence patterns to the maintenance of the coral-associated bacterial community.